Meeting others virtually in a day-to-day setting: Investigating social avoidance and prosocial behavior towards avatars and agents. (March 2018) - Felnhofer, Anna; Kafka, Johanna X.; Hlavacs, Helmut; Beutl, Leon; Kryspin-Exner, Ilse; Kothgassner, Oswald D.
Abstract: Given the increasing use of virtual characters, research is challenged to gain sufficient knowledge on the effects they may have on human cognitions, emotions and behaviors. Thus, this study set out to examine social avoidance tendencies and prosocial behaviors towards human controlled (avatars) and computer controlled entities (agents). A total of N = 95 healthy young adults were randomly assigned to an avatar or agent condition. Participants were exposed to a virtual stranger asking to sit at the table (prosocial behavior) as well as a virtual waiter handing over the false drink (social avoidance). Empathy, interaction anxiety, social and physical presence as well as subjective stress levels were assessed to control for confounding influences. Empathy emerged as a significant predictor of prosocial behavior. Social avoidance, in turn, was not predicted by any of the included variables. Also, there was no effect of agency on social presence, physical presence, social interaction anxiety and stress. Yet, participants showed significantly more social avoidance and prosocial behavior towards avatars. These seemingly contradictory results may be explained by an extension of prior theories: While intuitive responses (e.g., stress) follow the Media Equation Concept (Nass & Moon, 2000), more complex processes (e.g., empathy) may modulate agency dependent responses. Highlights: Empathy predicts prosocial behavior towards virtual characters. No differences in stress, social presence and physical presence regarding agency. Interacting with avatars leads to higher psychological involvement and empathy. Prosocial behavior and social avoidance are more likely with avatars than agents. No avatar-agent difference in intuitive reactions, but in complex responses.